Teknologi Informasi Efektif Mendeteksi Cyberbullying - Ajeng Ayu Kustianti; Renta Sianturi; Ameliya Sarwani; Anggita Putri Siswadi; Delia Nurmalita; Elisa Puspitasari (Journal of Bionursing, 2022)
Social media users are at risk for mental health disorders. Mental health problems can occur with cyberbullying. Cyberbullying that occurs on social media is in the form of rude comments, threats, insults, slander and even harassment given by netizens. Cyberbullying can shake a person's mental health condition and even have an impact on suicide. Cyberbullying will be very detrimental both mentally and productively. Cyberbullying must be detected early to prevent adverse effects on social media users. With advances in technology, it can be used to detect cyberbullying that occurs on social media. This article uses a literature review method approach, namely narrative literature review of 10 articles on the use of technology for cyberbullying detection in the period 2011 - 2021 with the aim of finding out cyberbullying comments on someone's account/post. Therefore, cyberbullying detection tries to collect global datasets on social media (Facebook, Instagram, Twitter, etc.), by classifying the Machine Learning method. Each algorithm method is evaluated using accuracy, precision, recall, and F1 score to determine the performance of the classification level